2017
DOI: 10.12816/0041522
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Opinions and Attitude of Surgeons in Saudi Arabia toward Informed Surgical Consent

Abstract: Background: Informed consent has become a vital factor for the clinical treatment of modern practice in the medical field, it is participating in legal, ethical and administrative compliance side. However, informed consent is variably applicable and rarely fulfills its theoretical ideal. Disclosure of adequate information is very important before signing informed consent. It is important to make patient enable to take a proper decision with good knowledge about his/her case. Informed consent for the surgical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Some saw consent as just a preoperative routine or simply signing a document because the consent process is strange to Saudi psychology. The majority were against the use of consent for all surgical procedures [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some saw consent as just a preoperative routine or simply signing a document because the consent process is strange to Saudi psychology. The majority were against the use of consent for all surgical procedures [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, doctors' and patients' levels of awareness and adherence to these guidelines in Saudi Arabia remain unclear and controversial. Thus, these findings create a basis for introducing formal informed consent training to make written information more accessible to doctors and patients [ 6 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,17,18 However, it has been shown in studies that verbal information was not given to the patients or it was not done at an adequate level. It was observed that 34% of surgical patients in Saudi Arabia 19 20.6% of orthopedic patients in Turkey 20 , and 13.6% of patients undergoing cardiac surgery 21 were not informed. The findings of the studies show that there is a decrease in the proportion of uninformed patients in Turkey and also in other countries.…”
Section: Discussionmentioning
confidence: 99%